HUBUNGAN PERHATIAN ORANG TUA DENGAN HASIL BELAJAR PESERTA DIDIK DI KELAS X SMA NEGERI 9 PADANG - Wati, Widya - (Bimbingan dan Konseling, 2014)
Family is education forum which have big effect toward students development.Therefore, students education can not separate with their family because family is the first forumto students learn. The aim of the research is describing about parents attention toward their childeducation, result of their lesson, correlation between parents attention toward students result inlearning. Types of research is correlational research. In other words the primary purpose of thisresearch to interpret a result or determine correlation between variable wich is studying. Theinstrument of the research is questionnaire. Referring of research finding and discussion, theresearcher conclude there are significant correlation between parents attetion with students resultof lesson at first grade of SMA Negeri 9 Padang, r hitung = 0,312 and r tabel 0,214 df 58 insiginificant level 0,05, validity= 95 %. It is mean that, r hitung â¥ r tabel.